2010
DOI: 10.1093/toxsci/kfq367
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Toxicology--A Brief Review of the Role of the Science in Shaping the Current Understanding of Air Pollution Health Risks

Abstract: Human and animal toxicology has had a profound impact on our historical and current understanding of air pollution health effects. Early animal toxicological studies of air pollution had distinctively military or workplace themes. With the discovery that ambient air pollution episodes led to excess illness and death, there became an emergence of toxicological studies that focused on industrial air pollution encountered by the general public. Not only did the pollutants investigated evolve from ambient mixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(98 citation statements)
references
References 177 publications
(184 reference statements)
0
90
1
7
Order By: Relevance
“…The UK Committee on the Medical Effects of Air Pollutants has also recently concluded that reductions in concentrations of both primary and secondary particles are likely to benefit public health (COMEAP, 2015). Nevertheless, although not conclusive, there is evidence that traffic-related sources of PM, or combustion sources more generally, are particularly associated with adverse health outcomes Schlesinger, 2007, 2010;Janssen et al, 2011;Stanek et al, 2011;WHO, 2013;Grahame et al, 2014). The possibility that primary PM 2.5 is more toxic per unit mass than secondary PM 2.5 , places greater emphasis on the finding from this work on the effectiveness of reductions in emissions of primary PM 2.5 .…”
Section: Discussionmentioning
confidence: 78%
“…The UK Committee on the Medical Effects of Air Pollutants has also recently concluded that reductions in concentrations of both primary and secondary particles are likely to benefit public health (COMEAP, 2015). Nevertheless, although not conclusive, there is evidence that traffic-related sources of PM, or combustion sources more generally, are particularly associated with adverse health outcomes Schlesinger, 2007, 2010;Janssen et al, 2011;Stanek et al, 2011;WHO, 2013;Grahame et al, 2014). The possibility that primary PM 2.5 is more toxic per unit mass than secondary PM 2.5 , places greater emphasis on the finding from this work on the effectiveness of reductions in emissions of primary PM 2.5 .…”
Section: Discussionmentioning
confidence: 78%
“…By definition, they address only a sole pollutant in the majority of circumstances, but this can be helpful when it's unclear whether the health effects reported in the real world are related to the actual pollutant or to a mixture of pollutants for which it acts as a tracer. For ozone, clear and extensive literature demonstrates its toxic potency, which has been well reviewed since 2005 (Stanek et al, 2011a; second draft of the EPA's integrated science assessment: EPA, 2012), though there remains the question of whether considering ozone alone underestimates the toxicity associated with the complete photochemical mixture. This point is addressed in the Answer to Question B4.…”
Section: Experimental and Panel Studiesmentioning
confidence: 99%
“…Air pollutants such as volatile organic compounds (VOCs) and fine particulate matter (PM 2.5 ) are associated with adverse health effects (Kampa and Castanas, 2008;Kim et al, 2013;Pedersen et al, 2014;Seagrave et al, 2006;Stanek et al, 2011). Since air pollutants are emitted from a variety of sources, identifying and quantifying source-specific contributions to the environment and health is needed to design effective control strategies (Heal et al, 2012;Lall et al, 2011).…”
Section: Introductionmentioning
confidence: 99%